Actividad física como estimulante de autovaloración en estudiantes. Universidad Nacional de Chimborazo, 2019 - Rodríguez Gómez, Mario Javier (2019)
Physical Activity as a stimulant of self-assessment in students. National University of Chimborazo, 2019 ABSTRACT: This research project is related to physical activity as a stimulant of self-assessment in the students of the National University of Chimborazo. Its main objective is to investigate physical activity and self-assessment in university students. The working population was 2740, using as a sample of 192 university students belonging to the first semesters of the different careers of the Faculty of the Health Sciences. They become a probabilistic sample consisting of 139 female students which is equivalent to 72.4%; and 53 male students equivalent to 27.6% who are between 17 and 34 years old, this research was based on a type of analytical and field research with a cross section and qualitative-quantitative nature. The survey was used as a research technique with the instrument called Displacement Questionnaire in University students, which included the IPAQ physical activity questionnaire in a short version of 4 questions and the D.D. Self-assessment Scale Questionnaire by W.W.K. ZUNG, for the tabulation of data was performed with the statistical program SPSS version 22 IBM, USA and we obtained as a result that students have a high level of physical activity with 48.4% and an acceptable self-assessment with 87.5% so it is recommended to encourage and encourage the practice of physical activity to improve these levels.